New horizons: Nutrition in the 21st century - Gillespie, Stuart; Hodge, Judith; Pandya-Lorch, Rajul; White, Jessica; Yosef, Sivan (International Food Policy Research Institute, 2016)
BY WEAVING STORIES together with analysis and description in this book, we have sought to convey the variety of experiences in tackling malnutrition in different contexts throughout the past five decades. This narrative approach is intended to help the reader translate an experience into his or her own context, showing many examples of what can be done and how success can be achieved. Our aim is not only to inform action, but to inspire.